2023
DOI: 10.20524/aog.2023.0772
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of pancreatic walled-off necrosis

Abstract: Pancreatic walled-off necrosis (WON) is a complication of severe pancreatitis. Endoscopic transmural drainage has been recognized as the first-line treatment for pancreatic fluid collections. Endoscopy offers a minimally invasive approach when compared to surgical drainage. Today, endoscopists may choose to use self-expanding metal stents, pigtail stents, or lumen-apposing metal stents to facilitate drainage of fluid collections. Current data suggest that all 3 approaches yield similar outcomes. It was previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that minimally invasive surgery (MIS) can effectively treat such conditions. Specifically, laparoscopic cystogastrostomy with internal debridement has been found to be superior to open surgical necrosectomy with internal debridement performs better than open surgical necrosectomy [ 8–12 ]. During the endoscopic drainage procedure, an internal endoprosthesis is inserted endoscopically to facilitate transluminal drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that minimally invasive surgery (MIS) can effectively treat such conditions. Specifically, laparoscopic cystogastrostomy with internal debridement has been found to be superior to open surgical necrosectomy with internal debridement performs better than open surgical necrosectomy [ 8–12 ]. During the endoscopic drainage procedure, an internal endoprosthesis is inserted endoscopically to facilitate transluminal drainage.…”
Section: Introductionmentioning
confidence: 99%